Variation in brown rat cranial shape shows directional selection over 120 years in New York City. Issue 11 (15th April 2020) - Puckett, Emily E.; Sherratt, Emma; Combs, Matthew; Carlen, Elizabeth J.; Harcourt‐Smith, William; Munshi‐South, Jason
Abstract: Urbanization exposes species to novel environments and selection pressures that may change morphological traits within a population. We investigated how the shape and size of crania and mandibles changed over time within a population of brown rats ( Rattus norvegicus ) living in Manhattan, New York, USA, a highly urbanized environment. We measured 3D landmarks on the cranium and mandible of 62 adult individuals sampled in the 1890s and 2010s. Static allometry explained approximately 22% of shape variation in crania and mandible datasets, while time accounted for approximately 14% of variation. We did not observe significant changes in skull size through time or between the sexes. Estimating the P‐matrix revealed that directional selection explained temporal change of the crania but not the mandible. Specifically, rats from the 2010s had longer noses and shorter upper molar tooth rows, traits identified as adaptive to colder environments and higher quality or softer diets, respectively. Our results highlight the continual evolution to selection pressures. We acknowledge that urban selection pressures impacting cranial shape likely began in Europe prior to the introduction of rats to Manhattan. Yet, our study period spanned changes in intensity of artificial lighting, human population density, and human diet, thereby altering various aspects of rat ecology and hence pressures on the skull. Abstract : Urbanization exerts unique selective pressures on wildlife populations. We observed directional changes in brown rat skull shape over 120 years for the population living in Manhattan, New York.